Superendividamento empresarial - Lages, Leandro Cardoso (2017)
This paper addresses the corporate over-indebtedness, especially the assumption of civil liability of financial institutions for the facilitated granting of credit to over-indebted companies that will not be able to meet the new financial obligations and, for this reason, will suffer with the increase of debt due to the incidence of interest and default charges, with repercussions on the default of financial obligations with other creditors. Therefore, the genesis of the work is based on the following question: Is there a responsibility for the financial institution that grants credit to a company that it is known that it will not be able to honor with the commitment assumed? If so, what are the contours of this responsibility? At first, the legislative matrix of over indebtedness is analyzed, whose concept arose in the Consumer Law, but also can reach the business activity. Subsequently, the mechanisms of analysis of credit risk, used by financial institutions and that allows them to check the possibility of payment of the applicants to credit, are verified. Finally, it is addressed the hypothesis of civil liability of financial institutions for the granting of credit to over-indebted companies focusing on the social function of contracts, the duty of collaboration, as well as the principles of company preservation, inherent risk and linkage to contracts. In the whole work there is reference to the repercussion of the debate on the legal protection of private investment